Smooth Transition Control Strategy for Operation Modes of Optical Storage Microgrid based on VSG - Huang, Guiping; Xia, Yan; Yang, Kai (International Journal of Natural Resources and Environmental Studies, 2024)
Addressing the challenge of suppressing voltage and frequency oscillations during mode transitions and achieving smooth transitions between grid-connected and islanded operation modes in peer-to-peer structured optical storage microgrids, is an urgent technical issue. This paper proposes a control strategy for smooth mode transitions based on numerical soft starters, focusing on the dynamic characteristics of voltage and frequency in optical storage microgrids during grid-connected and islanded operation modes. The numerical soft starter smoothens the input reference value of the current inner loop, reducing the impact of transient surge current on the current inner loop during transitions, thus ensuring the oscillations of bus voltage and frequency during microgrid mode transitions. In islanded operation mode, a VSG control strategy is introduced by constructing a small signal model to analyze the frequency response characteristics of the system under different inertia and damping characteristics, setting appropriate control parameters to provide strong frequency support for the system during islanded operation. Finally, an optical storage microgrid system is established using Matlab/Simulink to conduct simulation experiments under conditions such as grid-connected/islanded mode transitions, load fluctuations, and sudden changes in photovoltaic output power, validating the effectiveness of the proposed smoothing strategy.